Nelson Rodrigues, miséria e redenção: uma análise da obra rodriguiana pela perspectiva cristã - Curado, Beatriz Leme (2007)
In the present study we try to settle up a dialogue between the Christian tradition and the universe created by the Brazilian writer Nelson Rodrigues. We chose as reference inside the Christian tradition a philosophic religious system from the II century Gnosticism , and the tradition lead by Saint Augustine, Bishop of Hippo. In the first chapter, we estabilish a Brazilian s dramaturgic historic panorama. After that, we focus in Nelson Rodrigues life and work, giving emphasis in the religious influences that he may had suffer. In the following chapter we will find a brief historical panorama of Gnosticism; an explicitation of its structure, anthropology and gnosis importance. The peculiarities of the Valentinian system and the possible contact and divergence areas between this system and the universe created by Nelson Rodrigues. Then in the third chapter, we stress the Augustine tradition and the idea of caritas. To this it is necessary a concise explanation about human nature and grace. As a consequence we can evaluate the work of Nelson Rodrigues and find its resemblance with the Augustine s tradition. Finally at the fourth and last chapter we try to estabilish a parallel between the two religious traditions analyzed and the Nelson Rodrigues play Otto Lara Resende ou Bonitinha, mas ordinária